Current-rate flash sintering of gadolinium doped ceria: Microstructure and Defect generation. (1st May 2020) - Mishra, Tarini Prasad; Neto, Rubens Roberto Ingraci; Raj, Rishi; Guillon, Olivier; Bram, Martin
Abstract: In current-rate flash-sintering experiments the current is injected into the specimen from the very start and then increased at a constant rate, while the furnace is held at a constant temperature. The power supply remains under current control. The flash is induced at low current densities which reduces local heating at the electrodes. It leads to a uniform grain size across the entire gage length of the dog-bone specimen. This work pertains to 10 mol.% gadolinium-doped ceria flash sintered at current-rates ranging from 50 mA min −1 to 1000 mA min −1 at a furnace temperature of 680 °C. Full densities are obtained at a current density limit of 200 mA mm –2 . Densification is shown to depend only on the instantaneous value of the current density, and not on the current-rate. The grain size, however, is shown to become finer at higher current-rates. A preliminary analysis of the "energy deficit", that is, the estimated power input corresponding to the temperature as measured with a pyrometer, and the actual power consumption, estimates that huge concentrations of Frenkel defects may be introduced in the flash process. Graphical abstract: Image, graphical abstract